2014
DOI: 10.1245/s10434-014-3830-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Validation of the Prognostic Value of the Neutrophil-to-Lymphocyte Ratio for Upper Tract Urothelial Carcinoma Treated with Radical Nephroureterectomy

Abstract: This multi-institutional study revealed that elevated pre-NLR was significantly associated with worse pathological features such as tumor grade 3, advanced pT stage, positive LVI, and lymph node involvement in RNU specimens, and elevated pre-NLR was an independent risk factor of disease recurrence and cancer-specific mortality in UTUC patients treated with RNU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 30 publications
3
53
3
1
Order By: Relevance
“…However, adjusted for standard pathologic prognostic factors in UTUC, NLR did not retain statistical significance. Most of the previous studies reported, however, independent predictive value for RFS [15], CSS [13,14] and OS [14]. The discrepancies between these studies and our findings could be explained by several reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, adjusted for standard pathologic prognostic factors in UTUC, NLR did not retain statistical significance. Most of the previous studies reported, however, independent predictive value for RFS [15], CSS [13,14] and OS [14]. The discrepancies between these studies and our findings could be explained by several reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Altered NLR was associated with features of biologically and clinically aggressive UTUC such as advanced tumor stage, LVI, tumor necrosis, sessile architecture and lymph node metastases. These findings confirm the results reported in smaller cohorts [13][14][15]. The potential reasons for such associations remain hypothetical.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations